2016
DOI: 10.1089/jwh.2015.5674
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Vaccine-Type Human Papillomavirus Does Not Differ by Race or Ethnicity Among Unvaccinated Young Women

Abstract: Background: Previous studies have demonstrated racial and ethnic differences in the distribution of human papillomavirus (HPV) types among adult women with cervical precancers. The aim of this study was to determine whether the distribution of vaccine-targeted HPV types varies by race/ethnicity among unvaccinated young women. Materials and Methods: A secondary analysis was performed using data from four studies of sexually experienced, unvaccinated, 13-26-year-old women. Participants completed surveys and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The results from our study also indicate that much of the decrease in vaccine-type HPV [31] demonstrated in the US could be due mainly to decreases among young white women. We observed that the prevalence of high-risk vaccine-type HPV did not vary significantly by race/ ethnicity during the prevaccine years, similar to evidence reported among unvaccinated young women [3234]. Although young black women experienced a modest decrease in prevalence of vaccine-type HPV, the decrease did not occur until late post-licensure years (2011–2014).…”
Section: Discussionsupporting
confidence: 83%
“…The results from our study also indicate that much of the decrease in vaccine-type HPV [31] demonstrated in the US could be due mainly to decreases among young white women. We observed that the prevalence of high-risk vaccine-type HPV did not vary significantly by race/ ethnicity during the prevaccine years, similar to evidence reported among unvaccinated young women [3234]. Although young black women experienced a modest decrease in prevalence of vaccine-type HPV, the decrease did not occur until late post-licensure years (2011–2014).…”
Section: Discussionsupporting
confidence: 83%
“…In a second study, African American and Hispanic women had a lower prevalence of HPV16 or 18 in CIN2+ lesions compared with Caucasian women [14]. Additional recent studies (but not all) found low HPV16 and sometimes also HPV18 among African Americans in the general population, even in the absence of cervical precancer [1520]. One prior study in women with HIV by Whittemore et al (2016) did not find similar racial differences, but studied young individuals, 13–26 years of age, without cervical precancer.…”
Section: Introductionmentioning
confidence: 99%